Platelet Distribution Width and Preeclampsia: A Meta-Analysis - Awad-Elkareem Abass (Pakistan Journal of Medical & Health Sciences, 2022)
Many research findings have determined the platelet distribution width (PDW) in preeclampsia; no published meta-analysis existed. The aim of this review is to evaluate the reported PDW differences in preeclamptic women compared to healthy pregnant women. A Scopus, Pubmed-NCBI, ScienceDirect-open access and Google scholar Database were searched for a period of Jan 2010 to Apr 2020. OpenMeta Analyst software was used to compute the pooled Meta-logistic regression. A 13 study were included; with a total of 1143 preeclampsia and 1725 normal pregnant women control. The mean (SD) of the PDW level was significantly higher in preeclampsia compared to controls [14.52 (2.61) % vs. 13.0 (2.55) %, P < 0.001]. Seven studies compared the PDW level in the mild with severe preeclampsia. It was significantly higher in severe compared to mild preeclampsia [16.38(2.45) % vs. 14.55 (2.57) %, P < 0.001]. Finding of this meta-analysis suggests that PDW represents a promising biomarker for the detection of patients with preeclampsia.